Orthopedic surgical practice in context of the COVID-19 pandemic - Ratko Yurac B; Juan J Zamorano; Carlos Valderrama (Journal of Surgery and Surgical Research - Peertechz Publications, 2020)
On December 31, 2019, a new strain of coronavirus (SARS CoV-2) was notified for the first time in Wuhan (China). This disease (COVID-19) spread rapidly throughout the world, being declared a global pandemic by the WHO on March 11, 2020 [1], reaching the impressive figures of 24,537,560 cases diagnosed with 832,879 deaths in the world so far [2]. The literature has been growing and diverse in the knowledge about the catastrophic nature of this pandemic, which has undoubtedly strongly affected almost every country in the world.